THE HISTORY OF STUDYING MULTI-COMPONENT COMPLEX SENTENCES IN GENERAL AND TURKIC LANGUAGE EDUCATION (Academicia Globe: Inderscience Research, 2024)
This article analyzes the history of studying multi-component compound sentences in general linguistics and Turkic languages. Compound sentences are one of the complex linguistic units in terms of language structure and grammar, and their unique characteristics and classification are examined. The article highlights the history of studying compound sentences in Turkic languages, particularly focusing on the Karakalpak language and scientific developments in this area. Additionally, modern technologies for studying multi-component compound sentences in contemporary linguistics are reviewed.